Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Lansia Komorbid Masa Pandemi COVID-19 Di Puskesmas I Negara - Yurida Ananda Aprillia; Dwi Prima Hanis Kusumaningtiyas; I Ketut Andika Priastana (Indonesian Journal of Health Research, 2022)
Introduction. Anxiety is fear or worry in certain very threatening situations that can cause anxiety because of uncertainty in the future and fear that something bad will happen. Anxiety in the elderly during the pandemic causes an impact on the decline in physical activity and functional status of the elderly, such as having feelings of worry, not sleeping well, and disturbed appetite. Efforts that can be made to reduce the level of anxiety in the elderly are through family support. Methods. This study used a cross sectional design. The population in this study were the elderly who were in the working area of ​​the Public Health Center I Negara as many as 70 respondents. The sample of this research used purposive sampling technique. The analysis of this study used the Spearman rho test. Results. This study found that the results of family support in the working area of ​​Public Health Center I Negara mostly had sufficient scores and the results of anxiety that most of the elderly experienced mild anxiety. The results of the research analysis state p-value = 0,000 (p< 0,01). Conclusion. There is a relationship between family support and the anxiety level of the comorbid elderly during the COVID-19 pandemic at Public Health Center I Negara.